2021
DOI: 10.3390/f12070833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Leaching on Photodegraded Scots Pine and Spruce Timbers Monitored by FTIR Spectroscopy

Abstract: The goal of this research was the systematic study and comparison of the divided individual effects of UV light irradiation and water leaching during artificial weathering. Spruce (Picea abies Karst.) and Scots pine (Pinus sylvestris L.) samples were irradiated by ultraviolet (UV) light. Another sequence of samples was treated with the combination of UV irradiation and water leaching. The total extent of UV treatment was 20 days for both series of samples. Time relation of UV irradiation and water leaching was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Similar results had been obtained by [38], who found a decrease in the peak at 1510 cm −1 to 60% of the original absorbance value when the spruce wood was irradiated with UV light. In addition to the decrease in the peak at 1508 cm −1 , reduced absorbance was also observed around 1470 cm −1 (aromatic deformation of the C-H) and at 1264 cm −1 (guaiacyl ring breathing), which agrees with the results obtained with UV irradiation and the water leaching of Scots pine and spruce wood [39][40][41]. Several authors found a strong decrease in the absorbance of lignin in wood during the photodegradation process associated with the formation of carbonyl groups [38,41,42].…”
Section: Ftir Spectroscopysupporting
confidence: 89%
“…Similar results had been obtained by [38], who found a decrease in the peak at 1510 cm −1 to 60% of the original absorbance value when the spruce wood was irradiated with UV light. In addition to the decrease in the peak at 1508 cm −1 , reduced absorbance was also observed around 1470 cm −1 (aromatic deformation of the C-H) and at 1264 cm −1 (guaiacyl ring breathing), which agrees with the results obtained with UV irradiation and the water leaching of Scots pine and spruce wood [39][40][41]. Several authors found a strong decrease in the absorbance of lignin in wood during the photodegradation process associated with the formation of carbonyl groups [38,41,42].…”
Section: Ftir Spectroscopysupporting
confidence: 89%
“…The ageing of materials is an irreversible, in-time occurring complex phenomenon, affecting both wood surfaces and the coating materials. The main ageing factors include temperature, light/UV radiation, humidity, and oxygen exposure, which can lead to different chemical degradation processes, such as photolysis (photodegradation), thermolysis (thermodegradation), and oxidation [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The photodegradation of wood continues to be a subject of wide interest. Many different investigations have demonstrated that wood photodegradation is primarily related to the decomposition of lignin by UV radiation [11,[43][44][45][46][47]. Lignin absorbs much more UV radiation than cellulose and hemicellulose, resulting in colour and surface chemical changes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] The peaks at ≈1581 and 1764 cm −1 were attributed to the C–O and C═O stretching, respectively. [ 24 ] XPS measurements were also conducted (Figure S5 , Supporting Information). The O1s peaks at 531.52 and 532.73 eV, indicating O–H and C═O, respectively.…”
Section: Resultsmentioning
confidence: 99%